The arrow- debreu's model is a static model (1997)
This article, which tomis part of a wider study, presents the Arrow-Debreu's model, analyzing some of its theoretical limitations. Its main objective is to show that the model is static and that dynamic considerations can not be inferred from it. Besides, it shows that most misinterpretations of the model arise from considering it a dynamic modelo